(untitled) (Indonesian Journal of Science and Technology, 2025)
This paper aims to determine the distribution of light intensity values in a room at a certain time using a Light Dependent Resistor (LDR) sensor by comparing the light intensity and sensitivity of the LDR in conditions of changing dark to light in the room. The distribution of light intensity is measured using a light sensor assisted by Arduino application, the results of the average light intensity value when changing from dark to light conditions will automate the lights to turn on and off. Thus, it is hoped that it can save electricity. This experiment was integrated with the engineering design process through the following stages: 1) Identification of the problem, 2) Discussion of problem-solving, 3) Designing, 4) Creating, redesigning, and evaluation tests, and 5) Sharing solutions. Indoor light intensity measurements were carried out for 7 days, from 00.00, to once every 3 hours the distribution of the light intensity values read was checked. The research results provide new findings that the average distribution of light when changing from dark to light at 05.36 - 05.37 indoors shows a value of 105-135 lx, while from light to dark at 18.07 - 18.08 shows a value of 75 - 88 lux. These results can be used in further research to determine values that can be input into coding to control LDR sensor automation in product development.